EXPLORING VOCABULARY DEVELOPMENT IN A TWO-YEAR-OLD: A CASE STUDY OF SALMA THROUGH THE LENS OF PIAGET’S COGNITIVE DEVELOPMENT THEORY - Kukuh Satria; Zami Aqil Alkhobir; Mohamad Dafa, R.N; Nargis (Media Inovasi Pendidikan dan Publikasi, 2024)
This journal explores the vocabulary development of a two-year-old child named Salma, using Jean Piaget's cognitive development theory as the analytical framework. This research adopts a qualitative case study design to explore vocabulary development. By observing Salma's interactions within her natural environment and through parental interviews, this research identifies significant milestones in her language acquisition. Key findings include Salma's mastery of object permanence, engagement in symbolic play, and the formation of two-word phrases, all of which align with Piaget's sensorimotor stage. The role of responsive parenting and the quality of maternal speech are highlighted as crucial factors in Salma's rapid vocabulary growth. This case study underscores the importance of providing language-rich environments and encourages the integration of Piaget’s theoretical insights into early childhood education practices to foster cognitive and linguistic development.